Synchronisation of vascular ultrasonic scans with heart activity using ECG signals - Bener, Omer Faruk (2010)
Diagnosis, monitoring and curing of various vascular abnormalities can be linked to measurements of wall thicknesses of blood vessels. However, use of echo ultrasonic signals for these measurement is complicated by the low level of reflections from the vessels (1-2% from the incident energy), which results in considerable noise. Since the changes in thickness to be monitored are very small, this requires operation of ultrasonic scanners at high sampling frequencies, much higher than 50–100 MHz sampling frequencies that are used by contemporary ultrasonic scanners. That is because the resolution of the measured thickness is dependent on the time domain resolution of the recorded echoes; the latter is determined by the sampling frequency. An additional issue is the variability in the blood vessel wall thickness depending on the phase of the heart activity. Several studies show that these variations with a cycle time of around one second result in the same changes as building atherosclerosis for one year.